Intra-Species Diversity of Leishmania major and L. tropica from Clinical Isolates of Cutaneous Leishmaniasis in Southwest Iran Inferred by ITS1-rDNA - MIRZAPOUR, Aliyar (Iran J Public Health, 2019)
BACKGROUND: Cutaneous leishmaniasis (CL) as a public health concern is increasingly circulating by causative agents of Leishmania tropica and L. major in Iran. As regard to recent treatment failure and controlling problems, the accurate elucidation of heterogeneity traits and taxonomic status of Leishmania spp. should be broadly addressed by policymakers. This study was designed to determine the genetic variability and molecular characterization of L. major and L. tropica from Iranian CL patients. METHODS: One hundred positive Giemsa-stained slides were taken from clinical isolates of CL at Pol-e-Dokhtar County, Southwest Iran, from May 2014 to Sep 2016. DNAs were directly extracted and amplified by targeting ribosomal internal transcribed spacer (ITS) gene following microscopic observation. To identify Leishmania spp. amplicons were digested by restriction enzyme HaeIII subsequent PCR-RFLP technique. To reconfirm, the isolates were directly sequenced to conduct diversity indices and phylogenetic analysis. RESULTS: Based upon the RFLP patterns, 84 and 16 isolates were explicitly identified to L. tropica and L. major respectively. No co-infection was found in clinical isolates. The high genetic diversity of L. tropica (Haplotype diversity 0.9) was characterized compared to L. major isolates (Hd 0.476). The intra-species diversity for L. tropica and L. major isolates corresponded to 3%–3.9% and 0%–0.4%, respectively. CONCLUSION: Findings indicate the L. tropica isolates with remarkable heterogeneity than L. major are predominantly circulating at Pol-e-Dokhtar County. Occurrence of high genetic variability of L. tropica may be noticed in probable treatment failure and/or emerging of new haplotypes; however, more studies are warranted from various geographic regions of Southwest Iran, using large sample size.